2008
DOI: 10.1080/19393210802236893
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, cadmium and lead levels in samples of the main traded fish and shellfish species in Galicia, Spain

Abstract: The presence of mercury, cadmium and lead has been studied in raw and processed fish and shellfish of the main traded species in Galicia (Spain) from at least 40 commercial outlets between January 2002 and October 2003. The results show that, according to European legislation, the products on the market are generally "safe", although the high levels of mercury in swordfish and shark are notable, with 22% of samples (n = 37) over the limit. We also indicate the relatively important contribution to mercury inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
2
11
0
1
Order By: Relevance
“…Mercury contents for Atlantic Bonito samples throughout year were below the limits and the limits horse mackerel exceeded in October. Mercury levels in the literature were reported 0.12 mg kg )1 for muscles of mackerel (Blanco et al, 2008), 0.03 for muscles of horse mackerel, 0.04 for muscles of mackerel (Yusa´et al, 2008). The maximum contents of cadmium and lead were 0.161 mg kg )1 (February) and 0.355 mg kg )1 (March) for Atlantic Bonito (Table 4), respectively.…”
Section: Metal Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Mercury contents for Atlantic Bonito samples throughout year were below the limits and the limits horse mackerel exceeded in October. Mercury levels in the literature were reported 0.12 mg kg )1 for muscles of mackerel (Blanco et al, 2008), 0.03 for muscles of horse mackerel, 0.04 for muscles of mackerel (Yusa´et al, 2008). The maximum contents of cadmium and lead were 0.161 mg kg )1 (February) and 0.355 mg kg )1 (March) for Atlantic Bonito (Table 4), respectively.…”
Section: Metal Analysismentioning
confidence: 91%
“…Cadmium levels in the literature were reported 0.47 mg kg )1 for muscles of horse mackerel, 0.09 mg kg )1 for muscles of bonitos (Tu¨zen, 2003), 0.50 mg kg )1 for muscles of Atlantic horse mackerel, 0.90 mg kg )1 for muscles of Atlantic Bonito (Uluozlu et al, 2007), 0.01 mg kg )1 for muscles of mackerel and horse mackerel (Yusa´et al, 2008). Lead levels in the literature were reported 0.85 mg kg )1 for muscles of horse mackerel, 0.22 mg kg )1 for muscles of bonitos (Tu¨zen, 2003), 1.03 mg kg )1 for muscles of Mediterranean horse mackerel (Yılmaz, 2003), 0.68 mg kg )1 for muscles of Atlantic horse mackerel, 0.76 mg kg )1 for muscles of Atlantic Bonito (Uluozlu et al, 2007), 0.10 mg kg )1 for muscles of mackerel (Blanco et al, 2008), 0.04 mg kg )1 for muscles of mackerel, 0.03 mg kg )1 for muscles of horse mackerel (Yusa´et al, 2008).…”
Section: Metal Analysismentioning
confidence: 98%
“…Blanco, González, and Vieites (2008) also studied Hg in canned and frozen tuna, having obtained values ranging from <0.10 to 0.87 and from <0.10 to 0.49 mg kg À1 , respectively. Yusà et al (2008) observed Hg values in tuna varying from 0.02 to 2.5 mg kg À1 .…”
Section: Mercurymentioning
confidence: 99%
“…Tuna has been estimated to be amongst the most relevant Hg sources worldwide [61,62,63,64,65]. Of particular note in more recent studies is that Hg from canned tuna may be less bioaccessible than Hg from raw tuna [51,66].…”
Section: Humansmentioning
confidence: 99%